IMPACT OF SHADING AND CHLORMEQUAT CHLORIDE ON LANTANA SPECIFIC LEAF AREA AND MINERAL CONTENT - A. Matsoukis; D. Gasparatos; A. Chronopoulou-Sereli (Journal of Animal and Plant Sciences, 2015)
The creation of high quality plants and their maintenance depends, primarily, on proper fertilization, deriving mainly from the knowledge of their nutrient requirements (NR). Spray-applied chlormequat chloride (CCC), at the concentrations of 3000 and 6000 mg L-1, has been reported to contribute to the production of attractively flowering Lantana camara L. subsp. camara (lantana) plants. However, no information is available about the NR of these plants. The effects of the aforementioned CCC concentrations plus 0 mg  L-1 (control) on specific leaf area (SLA) and leaf potassium (K), phosphorus (P), calcium (Ca), iron (Fe) and manganese (Mn) contents of lantanas were examined under the 0% and 66% shading levels. Chlormequat chloride (3000 and 6000 mg L-1) decreased, generally, SLA of lantanas compared to control, at both shadings. Increased SLA values were estimated with increased shading. Phosphorus content increased with the increased CCC concentrations at 66% shading level. Phosphorus and Fe contents increased while Ca and Mn decreased with the increasing shading. The results of our study may contribute to the planning of a fertilization program for CCC-treated Lantana plants, a promising genus in landscaping in many countries around the world.
Keywords: Chlormequat chloride; Lantana camara L.; nutrition; onium-type regulator; specific leaf area; photosynthetic photon flux